Development of a Bioprocess for the Production of Cyclic Lipopeptides Pseudofactins With Efficient Purification From Collected Foam - Biniarz, Piotr; Henkel, Marius; Hausmann, Rudolf; Łukaszewicz, Marcin (Frontiers in Bioengineering and Biotechnology, 2020)
Microbial surfactants (biosurfactants) have gained interest as promising substitutes of synthetic surface-active compounds. However, their production and purification are still challenging, with significant room for efficiency and costs optimization. In this work, we introduce a method for the enhanced production and purification of cyclic lipopeptides pseudofactins (PFs) from Pseudomonas fluorescens BD5 cultures. The method is directly applicable in a technical scale with the possibility of further upscaling. Comparing to the original protocol for production of PFs (cultures in mineral salt medium in shaken flasks followed by solvent-solvent extraction of PFs), our process offers not only ∼24-fold increased productivity, but also easier and more efficient purification. The new process combines high yield of PFs (∼7.2 grams of PFs per 30 L of working volume), with recovery levels of 80–90% and purity of raw PFs up to 60–70%. These were achieved with an innovative, single-step thermal co-precipitation and extraction of PFs directly from collected foam, as a large amount of PF-enriched foam was produced during the bioprocess. Besides we present a protocol for the selective production of PF structural analogs and their separation with high-performance liquid chromatography. Our approach can be potentially utilized in the efficient production and purification of other lipopeptides of Pseudomonas and Bacillus origin.